Comparative analysis of query execution speed using Entity Framework for selected database engines - Krzysztof Winiarczyk; Rafał Stęgierski (Journal of Computer Sciences Institute)
This article presents the comparative analysis of time efficiency while executing queries by object-relational mapping framework Entity Framework for the following database engines: Microsoft SQL Server, MySQL and PostgreSQL. Time measurements of obtaining object results from database queries were made by app created in C#. Queries referred to single or multiple tables linked by relationships (1:1, 1:n, m:n) and performed operations of reading, creating, updating and deleting data. Obtained results have been cleaned from outliers and trimmed means were given as final results. Different database engines obtained the shortest query execution times depending on record number and table structures.